Influence of entropy generation on hybrid nanoparticles near the lower region of solid sphere - S. Sakinder; T. Salahuddin; Fahad S. Al-Mubaddel; Mohammad Mahtab Alam; Irfan Ahmad (Case Studies in Thermal Engineering, 2021)
In this paper, entropy generation effect on MHD boundary layer flow of hybrid nano-liquid with non-uniform viscosity near the lower stagnation region of heated sphere is examined. Hybrid nano-liquid is an innovative class of thermal liquids based nanotechnology and essentially it has been validated to enhance the energy conversion process competence. The flow of CH3OH liquid is diluted by adding alloy nanoparticles (a class of alumina) and their oxides are absolutely proficient to deflate the empirical scientific concerns related to quicker thermal transport. Governing PDEs are simplified and renovated into systems of ODEs and numerical solutions are executed by RK-4 based shooting scheme. We have also brought under discussion the impact of distinct substantial physical parameters of problem. A careful analysis discloses that thermal transfer rate of nano-liquid is immensely magnificent as compare to the mono nano-liquid. A close comparison exhibits that the hybrid nanosuspension offers elevated thermal distribution than usual nano-liquids.